Do University Studies in Social and Legal Field Teach Social Entrepreneur Competencies? - Palomares Montero, Davinia; Chisvert Tarazona, Maria José (Opción, 2015)
There is consensus on the potential of education to provide training related to entrepreneurship. However, teaching social entrepreneurship is different from teaching business competences. We apply the content analysis method to conduct a critical review of university degrees offered by universities. The units of analysis are 32 degree course outlines. Later on, the inventories were delivered to an expert group. Results show that moral and social dimensions awarded much lees importance while training is mainly focused on intellectual one. Moreover, expert team af- firms that moral and social competencies of social entrepreneurship are left in the hands of hidden curriculum. Â